Pemahaman Obejektivitas Oleh Wartawan(Studi Deskriptif Kualitatif Pemahaman Objektivitas Tim Redaksi Koran Pabelan di Universitas Muhammadiyah Surakarta) - Regar, Tiara Boru, Nur Latifah Umi Satiti, MA (2016)
Objectivity becomes ethics and moral values which should be held firmly by newspaper in running its journalistics proffesionalism. Besides, it can be central value which underlies disipline aspect of proffesionalism aspired by the journalists themselves. This research aimed to describe the objectivity of reporting issued by Pabelan newspaper and the understanding of the board of editors of Pabelan. The subjects of this research were Chief of editor, operational editor, editors, and two journalists of Pabelan newspaper. Method of the reserach applied qualitative-descriptive method which digged up deeply the phenomena arisen and described the results taken from the field. Using deep interview to the informant about the objectivity of reporting, the researcher compared the results of interview with the news published by Pabelan newspaper. The results of the studies that have been obtained through in-depth interview to the informant that do not understand the objectivity according Westersthal perspective. Reporter Newspapers Pabelan still no conscience to meyuarakan the rights of students and there is mixing of the opinion in fact conducted by the newspaper reporter Pabelan. Not every reporter understands objectivity is one hundred percent only known public opinion should not be mixing in news writing and shall not favor to the informant.